Influence of contextual factors and continuous medical education on healthcare outcomes in the Republic of Serbia - Vuković Mira H. (Srpsko lekarsko drustvo, 2017)
Introduction: The basic purpose of the professional continuing education is facilitating the successful conduct of practitioners in the field of practical characteristics of their professional work. Topic: In the Republic of Serbia (RS), the current Ordinance on Closer Conditions for Continuing Education for Healthcare Workers and Healthcare Associates implies that there is a connection between continuing medical education (CME) and the improvement of quality of healthcare workers and healthcare associates. However, such connectivity is difficult to prove. In order for the CME programs to be effective in improving the quality of work of healthcare professionals, it is essential that the well-known criteria for assessing the effectiveness of the CME programs be implemented in the Ordinance of the RS. Conclusions: Strong application of the criteria for assessing the effectiveness of the CME program can lead to improvement of the performance of the healthcare professionals, patient outcomes and the population's health in the RS.